Enhancing Akidah and Akhlak Understanding through Contextual Learning Model at MTs Futuhiyyah Bangorejo - Mohammad Ramli; M. Aris Fahruddin (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to investigate the effectiveness of the Contextual Learning Model in enhancing students' understanding of Akidah and Akhlak at MTs Futuhiyyah Bangorejo. Akidah and Akhlak are fundamental aspects of Islamic education that shape students' beliefs and moral behavior. However, traditional teaching methods often fail to connect these values with students' real-life experiences. The Contextual Learning Model, which emphasizes linking learning material to students' daily lives, is believed to offer a solution to this challenge. This study was conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. Data was collected through classroom observations, student assessments, and interviews with both students and teachers. The findings suggest that the Contextual Learning Model significantly improved students' ability to relate Akidah and Akhlak teachings to real-life situations. By incorporating local culture, daily experiences, and community involvement into the lessons, students were able to better understand and internalize the values of Akidah and Akhlak. Moreover, the model fostered increased student engagement, participation, and motivation in the learning process. This research concludes that the Contextual Learning Model is an effective approach to teaching Akidah and Akhlak, as it helps students apply Islamic values in practical, everyday contexts. The study offers valuable insights for educators seeking to implement more relevant and engaging teaching strategies in religious education.